Ammonia emissions from an anaerobic digestion plant estimated using atmospheric measurements and dispersion modelling. (October 2016) - Bell, Michael W.; Tang, Y. Sim; Dragosits, Ulrike; Flechard, Chris R.; Ward, Paul; Braban, Christine F.
Highlights: We measure atmospheric ammonia concentrations around an anaerobic digestion plant. We estimate ammonia emission rates by a "bottom-up" emission factor and "top-down" inverse modelling methods. The storage and treatment of solid and liquid digestate on site were the greatest sources of ammonia emissions. Abstract: Anaerobic digestion (AD) is becoming increasingly implemented within organic waste treatment operations. The storage and processing of large volumes of organic wastes through AD has been identified as a significant source of ammonia (NH3 ) emissions, however the totality of ammonia emissions from an AD plant have not been previously quantified. The emissions from an AD plant processing food waste were estimated through integrating ambient NH3 concentration measurements, atmospheric dispersion modelling, and comparison with published emission factors (EFs). Two dispersion models (ADMS and a backwards Lagrangian stochastic (bLS) model) were applied to calculate emission estimates. The bLS model (WindTrax) was used to back-calculate a total (top-down) emission rate for the AD plant from a point of continuous NH3 measurement downwind from the plant. The back-calculated emission rates were then input to the ADMS forward dispersion model to make predictions of air NH3 concentrations around the site, and evaluated against weekly passive sampler NH3 measurements. As an alternative approach emission rates from individual sources within the plant were initially estimated by applying literature EFs to the available site parameters concerning the chemical composition of waste materials, room air concentrations, ventilation rates, etc. The individual emission rates were input to ADMS and later tuned by fitting the simulated ambient concentrations to the observed (passive sampler) concentration field, which gave an excellent match to measurements after an iterative process. The total emission from the AD plant thus estimated by a bottom-up approach was 16.8 ± 1.8 mg s −1, which was significantly higher than the back-calculated top-down estimate (7.4 ± 0.78 mg s −1 ). The bottom-up approach offered a more realistic treatment of the source distribution within the plant area, while the complexity of the site was not ideally suited to the bLS method, thus the bottom-up method is believed to give a better estimate of emissions. The storage of solid digestate and the aerobic treatment of liquid effluents at the site were the greatest sources of NH3 emissions.